Overexpression of Rho–GDP‐dissociation inhibitor‐γ inhibits migration of neural stem cells. Issue 11 (30th August 2013) - Wang, Jiao; Li, Xiao; Cheng, Hua; Wang, Kai; Lu, Wei; Wen, Tieqiao
<x xml:space="preserve">Abstract</x> Neural stem cell (NSC) migration relies heavily on the regulation of actin and microtubule cytoskeletons by Rho GTPases, which are critical regulators of key steps during NSC migration. However, the migration mechanism remains unclear. Rho–GDP‐dissociation inhibitor‐γ (Rho‐GDIγ) was identified as an important downregulator of the Rho family of GTPases, because of its ability to prevent nucleotide exchange and thus membrane association. This study investigates the role of Rho‐GDIγ in neural stem cells migration. Our results indicate that the overexpression of Rho‐GDIγ maintains NSCs in the stem cell state, meanwhile preventing NSC migration through inhibition of Rac1 expression, one of the Rho‐family GTPases. This study provides the basis for further study of the molecular mechanism of NSC migration. © 2013 Wiley Periodicals, Inc.